ANALISIS PENGARUH DEFISIT ANGGARAN TERHADAP NERACA PEMBAYARAN INDONESIA - Wahyu Indah Astuti; Ando Fahda Aulia; Darmayuda ' (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2017)
This study aims to determine the effect of budget deficit on the Indonesia’s balance of payment. Which was separated in to current account and capital account. This research was conducted nationally namely Indonesia from 2000 to 2015 and uses secondary file obtained from central bank of Indonesia and Ministry of Finance. This research uses descriptive quantitative research approaches and selecting methods Co-integration and Error Correction Model (ECM) to determine the influence of the budget deficit on the current account and capital account in the long term and the short term by using a computer application program Eviews 7.0. This research consists of two models of analysis of the results of the analysis of co-integration and Error Correction Model (ECM). Co-integration estimation result that reflects a long-term relationship is obtained that the negative effect on the budget deficit significantly current account and budget deficits are not significantly positive effect on the capital accunt. While the results of the estimation of Error Correction Model (ECM), which reflects the short-term relationships showed that the negative effect on the budget deficit in the current account and budget deficits significant positive effect on the capital account significant.Keywords : Budget Deficit, Balance Of Payment, Error Crrection Model.